Characterization of Cathepsin B in Mediating Silica Nanoparticle-Induced Macrophage Pyroptosis via an NLRP3-Dependent Manner - Ma L; Han Z; Yin H; Tian J; Zhang J; Li N; Ding C; Zhang L (Journal of Inflammation Research, 2022)
Lan Ma,1,2 Zhengpu Han,1,2 Haoyu Yin,1,2 Jiaqi Tian,1,2 Jing Zhang,3 Ning Li,3 Chunjie Ding,4 Lin Zhang2 1School of Public Health, Weifang Medical University, Weifang, 261053, People’s Republic of China; 2Clinical Medical Research Center for Women and Children Diseases, Maternal and Child Health Care Hospital of Shandong Province, Shandong University, Jinan, 250001, People’s Republic of China; 3School of Public Health, North China University of Science and Technology, Tangshan, 063210, People’s Republic of China; 4School of Public Health, Xinxiang Medical University, Xinxiang, 453000, People’s Republic of ChinaCorrespondence: Lin Zhang, Clinical Medical Research Center for Women and Children Diseases, Maternal and Child Health Care Hospital of Shandong Province, Shandong University, Jinan, 250001, People’s Republic of China, Tel +86-531-68795046, Email zhanglin8901@163.comIntroduction: Silica nanoparticles (SiNPs) are one of the most widely used inorganic nanomaterials, and exposure to SiNP has been demonstrated to induce pulmonary inflammation, primarily promoted by the NLRP3-mediated macrophage pyroptosis. However, mechanisms underlying the activation of NLRP3 signaling are complex, and whether cathepsin B (CTSB), an enzyme released by the ruptured lysosome, could trigger NLRP3 assembly is controversial.Methods: To further characterize the role of CTSB in silica-induced pyroptosis, we conducted this study by establishing SiNP exposure models in vitro. The morphological features of SiNPs were exhibited by the SEM and TEM, and the effects of SiNPs’ internalization on macrophages were examined by the TEM and immunofluorescent staining. Moreover, Western blot was performed to detect the expression of proteins related to pyroptosis and CTSB after blocking the expression of NLRP3 and CTSB.Results: We found that SiNPs internalization caused the rupture of macrophage membrane and promoted the aging of cells with increased intracellular vacuoles. Also, the expression of NLRP3, ASC, Caspase-1, GSDMD, Pro-IL-1β, IL-1β, and CTSB increased under the stimulation of SiNP, which could be suppressed by additional treatment with MCC950, an NLRP3-specific inhibitor. Besides, we found SiNP joint treatment with leupeptin, a CTSB inhibitor, could inhibit the expression of CTSB, but it had no effect on the expression of NLRP3, ASC, and Caspase-1, and the process of macrophage pyroptosis was also not affected.Conclusion: SiNP exposure induces rupture of macrophages and the release of lysosomal CTSB, but CTSB fails to specifically act on the NLRP3 inflammasome to induce pyroptosis which is causally linked to lung inflammation and fibrosis.Keywords: silica nanoparticles, NLRP3 inflammasome, cathepsin B, pyroptosis, macrophage